Optimalisasi Pemanfaatan Smartboard dalam Meningkatkan Efektivitas Kinerja Guru di SMP IT Mutiara - Qatrunnada, Qatrunnada; Hadijaya, Yusuf (Jurnal Pendidikan Madrasah, 2026)
This study examines the optimization of smartboard utilization in improving teacher performance effectiveness at SMP IT Mutiara. The research is motivated by the gap between the availability of digital learning technology and its optimal pedagogical utilization in classroom practices. A qualitative approach was employed using a case study design. Data were collected through in-depth interviews, observations, and documentation. The findings indicate that the utilization of smartboards at SMP IT Mutiara has developed positively, shifting from a conventional presentation tool to an interactive learning medium integrating multimedia resources such as videos, digital quizzes, educational games, and various online platforms. However, the level of utilization remains uneven among teachers and has not yet been fully optimized. Teachers generally perceive smartboards positively, as they facilitate material delivery, enhance student engagement, and create more interactive classroom environments. Nevertheless, limitations in training and digital pedagogical competence remain key challenges in maximizing their use. Furthermore, smartboard integration contributes significantly to improving teacher performance effectiveness, particularly in instructional creativity, classroom management, time efficiency, and student participation. Despite these positive impacts, technical constraints such as internet instability and limited professional training still affect implementation consistency. Overall, the study concludes that smartboards have strong potential to enhance teacher performance effectiveness; however, their optimization depends on teachers’ digital competence, continuous professional development, and adequate technological infrastructure.